Unemployment in reforming countries: Causes, fiscal impacts and the success of transformation - Volker Treier (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1999)
The paper addresses and summarizes the role of unemployment in the transformation process from an economic system with a dominant state sector to a system with a dominant private sector. After reviewing the basic facts and some of the main explanations why unemployment is high during transition in countries of Central and Eastern Europe the role of unemployment and the fiscal problems due to unemployment is discussed within a model of economies of transition. The model highlights the ambivalent role of unemployment. On the one hand unemployment could jeopardize the transformation process when it reaches a critical value but on the other hand it could be regarded as an unavoidable byproduct and even a necessary device for the success of the whole process. After presenting the main features and conclusions of the model concerning the role of unemployment, another point of view, which lets doubt about the necessity and temporariness of 'transitional unemployment', will be discussed.
Keywords: E24; H30; H60; P20; 330; Central and Eastern Europe; transition; unemployment; restructuring; fiscal dynamics; Arbeitslosigkeit; Übergangswirtschaft; Allgemeines Gleichgewicht; Öffentliche Finanzwirtschaft; Dynamisches Modell; Theorie